Cryptic fungal diversity revealed in deep-sea sediments associated with whale-fall chemosynthetic ecosystems - Yuriko Nagano; Toshiko Miura; Taishi Tsubouchi; Andre O. Lima; Masaru Kawato; Yoshihiro Fujiwara; Katsunori Fujikura (Mycology, 2020)
In this study, sediments from whale-fall chemosynthetic ecosystems (two different sites, one naturally occurring at 4200 m water depth in South Atlantic Ocean and one artificially immersed at 100 m water depth in Kagoshima Bay, Japan) were investigated by Ion Torrent PGM sequencing of the ITS region of ribosomal RNA to reveal fungal communities in these unique marine environments. As a result, a total of 107 (897 including singletons) Operational Taxonomic Units (OTUs) were obtained from the samples explored. Composition of the 107 OTUs at the phylum level among the five samples from two different whale-fall sites was assigned to Ascomycota (46%), Basidiomycota (7%), unidentified fungi (21%), non-fungi (10%), and sequences with no affiliation to any organisms in the public database (No-match) (16%). The high detection of the unidentified fungi and unassigned fungi was revealed in the whale-fall environments in this study. Some of these unidentified fungi are allied to early diverging fungi and they were more abundant in the sediments not directly in contact with whalebone. This study suggests that a cryptic fungal community exists in unique whale-fall ecosystems.